Terrorism and asymmetric conflict in Southwest Asia - Chubin, Shahram; Green, Jerrold D.; Rathmell, Andrew; Rand eBooks (Santa Monica, CA : RAND, 2002)
At two earlier RAND-GCSP workshops in 1999 and 2001, participants examined roles for NATO in the Middle East and Turkey's challenges as both a European and Middle Eastern actor. The 2002 workshop's agenda focused on terrorism and asymmetric conflict in Southwest Asia, from both a regional and global perspective. Continued instability in Southwest Asia has required a series of costly U.S. military interventions and is likely to pose a security problem in the future, as the United States becomes increasingly dependent on the region's supply of cheap oil. The workshop's 26 experts from Europe and the United States held discussions based around four main themes: military lessons from the Afghan campaign, terrorism and asymmetric warfare, regional dimensions of the conflict, and Euro-Atlantic relations in Southwest Asia. Since September 11, 2001, developments in Afghanistan, in the Middle East and the Gulf, and in trans-Atlantic relations have combined to pose serious questions for European and U.S. policy toward terrorism, Southwest Asia, and the conduct of international relations more generally. Although the United States and Europe share similar interests in relation to Southwest Asia, they have adopted divergent tactics toward the region.
"Center for Middle East Public Policy -- Geneva Center for Security Policy."
"Report of a Geneva Centre for Security POlicy/RAND workshop"--P. [1].
Conference held June 23-25, 2002.
Third in a series.
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Asymmetric warfare -- Asia, Central -- Congresses; Asymmetric warfare -- Middle East -- Congresses; Terrorism -- Asia, Central; Terrorism -- Middle East; Guerrilla warfare; United States -- Military policy; Electronic books